Supervisi Dalam Administrasi Pendidikan - Muhammad Ali Hanafiah (Sekolah Tinggi Agama Islam Sumatera Medan, 2017)
Supervision is an effort to help the development and upgrading of the parties in supervision so that they can carry out tasks predefined activities efficiently and effectively. The characteristics and properties of supervision there are two that are natural and that is good. Supervision also has the functions and duties that the Coordinator, Consultant, Group Leader, Evaluator. The purpose of supervision is to provide assistance to subordinates directly, so that subordinates have enough stock to be able to carry out tasks or jobs with good results and orient, train workers, lead, provide direction, and develop the skills of personnel.